Studying solutions for the fatigue of the FAST cable-net structure caused by the process of changing shape. (October 2015) - Jiang, Peng; Nan, Ren-Dong; Qian, Lei; Yue, You-Ling
Abstract The Five-hundred-meter Aperture Spherical Radio Telescope (FAST) is supported by a cable-net structure, whose change in shape leads to a stress range of approximately 500 MPa. This stress range is more than twice the standard recommended value. The cable-net structure is thus the most critical and fragile part of the FAST reflector system. In this study, we first search for a more appropriate deformation strategy that reduces the stress amplitude generated by the process of changing shape. Second, we roughly estimate the tracking trajectory of the telescope during its service life, and conduct an extensive numerical investigation to assess the requirements for fatigue resistance. Finally, we develop a new type of steel cable system that satisfies the cable requirements for construction of FAST.